Paw Patrol : Pups and the ghost pirate - Mason, Owen; Cohen, Devan; Degruijter, Deanne; Forrester, Katherine ([Place of publication not identified] : [Publisher not identified], 2015)
It's Halloween and Capt'n Turbot is having a party on an old pirate ship! When the ship mysteriously drifts out to sea captained by a 'ghost' the pups must save the ship and discover who the ghost is!
Owen Mason, Devan Cohen, Deanne Degruijter, Katherine Forrester.
Rating: TVY.
DVD, widescreen.
English or French dialogue; closed-captioned.
Keywords: Feature films; Children's films; Video recordings for the hearing impaired; Children's films; Feature films; Video recordings for the hearing impaired